Factores psicosociales asociados a la prostitución en un grupo de trabajadoras sexuales venezolanas habitantes del Distrito Especial, Turístico y Cultural de Riohacha (2021)
The main objective of this Research Work was to examine the role that the Diaspora of Venezuelan women plays today as sex workers, in Riohachera society and of government entities that have the responsibility of working with a population dedicated to prostitution in the regulation of sex. sex work in Riohacha. Different problems that afflict this population were identified, in addition, health aspects that are handled by district entities are disclosed, so that these people can have the knowledge and decide at some point to undertake or start their workforce in another way